Poland's Tourist Activity and Accommodation Base by Voivodeship - Kobylińska, Małgorzata (Olsztyn Economic Journal, 2024)
The purpose of the article was to find out the changes in the size of the accommodation base and the number of tourists in Poland regionally in 2018, 2020 and 2022, and to determine the changes that took place in tourism as a result of the SARS-CoV-2 coronavirus pandemic. Based on the analysis, it was found that the number of accommodations and the number of tourists in Poland in the years under study varied greatly among the provinces. The highest level of the analyzed values was in the provinces of Lesser Poland, Pomerania and West Pomerania. The lowest values were recorded in the Opole province. Due to the limitations of the pandemic, a significant decrease in the number of tourists visiting Poland in 2020 by 50%, including foreign tourists by about 70%, compared to 2018, can be noted.